The Development of an Orientation and Mobility Program for Parents of Children with Visual Impairment - Dewi, Andam; Aprilia, Imas Diana (Proceeding of International Conference on Special Education in South East Asia Region, 2022)
The ability of orientation and mobility (O&M) in children with visual impairment was still very low, so the dependence on sighted people was very high and this limited the activities of children with visual impairment themselves. On the other hand, the parents of these children did not have the ability on O&M and thus face difficulties in teaching their children to develop their O&M at home. Therefore, it was important to have an operational guideline to provide help for parents in teaching their children to be independent. The purpose of this study is to formulate a program for parents on how to teach O&M to their children. The study was carried out using the qualitative approach with the case study strategy; the in-depth interview, direct observation, participant observation, and documentation, were used to collect the data, and the O&M Attribute Checklist was adapted from Perkins Freedom Mobility LLC (2014) was used to portray the O&M competence profile of the parents. The subjects of this study were parents of children with visual impairment. The result of this study is in the form of a program formulation that was developed based on the analysis of assessment and field needs, including objectives, materials, methods, implementation procedures, and evaluations. The conclusion is that through the program guidelines that have been formulated, it is hoped that parents have the competence and will be easier to teach their children’s O&M skills so that children develop optimally. The implication is that families must be consistent in following the designed program guidelines.